The Relationship between Knowledge with Doctors and Nurses’ Compliance Level to Use PPE in Hospital Surgery Room during Pandemic Era - Ardi Artanto; Ratih Pratiwi; Hilma Tri Ayu Rizda (Faculty of Medicine, University of Jember, 2021)
Hospitals are not only as a place of treatment, but also as a health service facility that can be a source of infection for other people. Doctors, nurses and other medical personnel are often exposed to potential hazards in hospitals, thus requiring protection in the form of personal protective equipment (PPE). However, compliance with the use of PPE is not always high, which makes doctors and nurses more vulnerable to risk of occupational diseases in hospitals. In one of conducted studies, the conditions that were less compliant in using PPE for health workers were 30%. One of the things that might affect this level of compliance is knowledge about PPE. The purpose of this study was to determine the relationship between knowledge and compliance level to use personal protective equipment among doctors and nurses in operating room installation from a private hospital in 2020. Analytic observational by using cross sectional research design was used in this study. The population were all doctors and nurses at operating room installation of mentioned hospital above. Sampling was taken by total sampling method and 26 samples met the inclusion criteria. In this study, there were 23 respondents (88.5%) obeyed the use of personal protective equipment, meanwhile 3 respondents (11.5%) who did not. The 3 respondents were on loop or circular nurses. So, there was a significant relationship between the level of knowledge and compliance in the use of personal protective equipment with p-value = 0.027and OR=44. Keywords: personal protective equipment, knowledge level, compliance level